Astudy of knowledge about immunization amongst mothers of children below 5 years of age - Dr Pramila Ramawat; Dr V. P. Goswami (Pediatric Review: International Journal of Pediatric Research, 2018)
Objectives: To assess the knowledge and attitude of mothers regarding immunization of children below 5 years of age.Methodology: A cross sectional descriptive study was conducted among mothers having children below 5 years of age. All mothers were interviewed through a self-designed pretested structured questionnaire regarding immunization of their children and socio demographic profile.Results: Majority of the mothers were illiterate, belonging to low-income group and not aware about the diseases in national immunization program. Majority (77%) of children were completely immunized according to age. The reasons for incomplete vaccination were lack of awareness, knowledge, distance, cough, cold and others reasons like household work. Anganwadi workers and health care workers were the main source of information. A positive attitude was reflected from mother towards immunization.Conclusion: The knowledge of mothers about vaccination was found inadequate but attitude toward immunization was good.